Voltammetric study of the interactions of alkaline earth metal ions and melamine at different ph - Haque, Farhana; Khatun, Afroza; Bakshi, PK; Shaikh, AA (Bangladesh Journal of Scientific Research, 2016)
The electrochemical redox behavior of alkaline earth metal ions at different pH in acetate buffer solution has been investigated using cyclic voltammetric method at gold disk electrode (GDE). In the entire studied pH (3.68-6.23), metal ions show two cathodic and an anodic peak. The method has also been employed to observe the interaction of metal ions with melamine in acetate buffer solution. At all pH, a reasonably strong interaction occurs between metal ions and melamine at different metal ions/melamine molar ratio. However, maximum interaction takes place at 1:4 molar ratios of metal ions and melamine at pH 6.23. This is possibly the most suitable condition for alkaline earth metal-melamine interaction. Bangladesh J. Sci. Res. 27(1): 39-50, June-2014